EKSISTENSI SASTRA ANAK DALAM PEMBENTUKAN KARAKTER PADA TINGKAT PENDIDIKAN DASAR - Ayyubi Subhi Farahiba (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2019)
The impact of globalization can be seen from the emergence of some of the interesting phenomenon that afflicts young people, especially children in Indonesia. Various problems that characterize the world of education makes the noble values and behaviors wisdom as torpor. Efforts to es- tablish the character of the child to do one through children’s literature. The approach used in this research is descriptive qualitative. This article studies focus on the role of children’s literature in the formation of char- acter and learning of children’s literature relevant to build the character of students at the elementary level. Learning about the character of dis- cipline, honesty, responsibility, admit mistakes, religious, and others will be more effective if delivered through stories with characters that charac- ter. Through literature, the child will also be directed to think logically about the causal relations and childbirth imagination will significantly correlated with creativity so that children will be able to think creative- ly (creative thinking) to always be productive. As a form to convey or inject character education to students in literature there are some efforts that can be done by educators. Educators reveal the values contained in children’s literature with direct integration of character values are an integral part of these subjects. Literature learning in primary schools can be classified in three groups, namely; fiction learning, learning poetry, drama and learning.